Car ownership decisions in Norwegian households - Anne Brendemoen (Statistics Norway, Research Department, 1994)
In this paper, household's decisions regarding how many private cars to own are analyzed. The analysis is based on a particular multinominal logit type formulation that is consistent with a Stone-Geary utility function. The model is estimated on data from the Norwegian Expenditure Survey.
Keywords: 330; Car ownership; car costs; multinominal logit model.